Kajian Literatur tentang Sel Eukariotik pada Mikroorganisme (Jamur dan Protista) dalam Perspektif Mikrobiologi dan Pendidikan Biologi - Najwa Hasyifa; Elifia Dwi Utami; Rizky Afifah Alfi; Widia Azhari Saputri; Nabila Az Zahra; Nadia Rahma; Rimsa Desela Putri; Miftahul Khairani (Lembaga Pengembangan Kinerja Dosen, 2026)
Eukaryotic microorganisms, particularly fungi and protists, play a vital role in ecosystems, as well as in microbiology studies and biology education. The complex structure of eukaryotic cells, such as a true nucleus and membrane-bound organelles, enables these two groups to perform diverse physiological functions and adapt to their environments. This study aims to synthesize the literature on the structure and function of eukaryotic cells in fungi and protists and their implications for biology learning. The method used is a literature review with a descriptive qualitative approach through analysis of relevant scientific sources. The results of this study indicate that understanding the structure of eukaryotic cells in fungi and protists is not only important in the context of microbiology but also contributes to strengthening understanding of the concept of cell structure and function and making biology learning more contextual and meaningful.